Spatiotemporal Changes of Vegetation in the Middle Draa Valley Oasis: A Study Case of M’hamid El Ghizlane Oasis (Morocco) - Lamqadem, Atman Ait; Saber, Hafid; Rahimi, Abdelmejid (European Scientific Journal, ESJ, 2017)
During the last decades, The Middle Draa Valley (Southeast of Morocco) was subjected to various environmental problems which haves caused land degradation especially in the south of the Middle Draa (M’hamid oasis). This study aims to analyze the spatiotemporal changes of vegetation in the M’hamid oasis. Based on the Landsat images belonging to six separate periods during 1984 to 2016 and Geographical Information System (GIS) techniques, the pattern of spatiotemporal changes of vegetation cover in M’hamid oasis was analyzed based to visual interpretation and NDVI (Normalized Difference Vegetation Index) and supervised classified. For easier understanding of the causes and origins of these changes, we exploited statistical data survey from various local administrations (climatological, socio-economic data) and fieldworks. The results show that the total area of the oasis showed an oscillating decrease between 1984-1999 compared to 1999-2013 and a sharp increase after 2003 to 2007 and a moderate decrease from 2003 to 2016, with an area 3 times smaller than the initial date (loss of 22% of oasis area), correlated with a reduction of the habitants (loss of 21% between 1980 and 2016). Mass tourism, construction of the Mansour Eddahbi dam and the irregularities of the rains and the succession of years of drought led to a modification of the oasis ecosystem. Due to these climatic conditions, the oasis population are obliged to emigration thus they leave their fields which are threatened by sand encroachments, therefore accelerating the phenomenon of sand movements and consequently desertification.